The Role of Organizational Culture in Enhancing Talent Retention in the Hybrid Work Era - Isnawati Osman (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Modern organizations face increasing challenges in retaining talented employees as hybrid work becomes the dominant model of the post-pandemic era. While flexibility offers numerous benefits, it also risks weakening shared values and emotional connections that underpin organizational commitment. This study aims to identify the cultural dimensions that most strongly influence talent retention in hybrid work environments, examine possible mediating and moderating mechanisms between culture and retention, and propose culture-based strategies for human resource leaders. Employing a qualitative approach through a systematic literature study, the research synthesizes findings from ten peer-reviewed articles published between 2015 and 2025. Thematic analysis reveals that inclusivity, flexibility, employee well-being, collaboration, and organizational commitment are the most influential cultural dimensions driving retention. Furthermore, organizational citizenship behavior (OCB) and employee well-being serve as mediating factors, while organizational commitment moderates the culture–retention relationship. The results indicate that organizational culture acts as the strategic core of retention in hybrid settings, transforming from a background element into a dynamic ecosystem that binds employees through shared trust, fairness, and psychological safety. The study concludes that culture-driven strategies such as promoting cultural intelligence, flexible policies, and emotional support systems are critical for sustaining loyalty and engagement in hybrid organizations.